The History of Quail Management with Comments on Pen-Rearing - Edward L. Kozicky (National Quail Symposium Proceedings, 2017)
Quail were present in the Lower Oligocene about 40 million years ago. The remains of northern bobwhite (Colinus virginianus) have been found in Indian middens in the eastern United States, but these birds were not considered a preferred food. However, California quail (Callipep/,a californica) were a choice food of Native Americans. Bobwhite are the most prized species by sportsmen, with the California quail in second place. There is evidence that northern bobwhite reached unprecedented numbers over large geographical areas, especially along their northern range in the mid-1800's. California and Gambel's quail (C. gambelii) were abundant in the mid- to late-1800's. From a social standpoint, the importance of northern bobwhite in promoting sportsmanship afield has never been fully appreciated. The bobwhite created a gentleman's way of life in the South that is steeped in socially accepted tradition which has been fostered and respected by sportsmen through the years. By its very nature, bobwhite hunting brings out the best in men and dogs. The eternal pursuit of perfection by man has made quail the hunting sport of choice by Americans. With ever-decreasing quail habitat and a growing human population, there is a great need to establish more quail habitat throughout the bird's range, and to produce pen-reared bobwhite that consistently emulate the sporting challenge of their wild cousins.
Keywords: history; pen-reared; private initiative; quail; social